We'll let that number be a variable 'x'

Now write the equation in terms of x just as you described;

x

Now solve. Since it's second order, we'll probably get two answers.

x

(x - 3)(x - 1) = 0

x = 3, x = 1

Now check the answers

x

(3)

9 = -3 + 12

so that one checks

(1)

1 = -3 + 4

and that checks too.

So the answers are 3 and 1.

Now write the equation in terms of x just as you described;

x

^{2}= -3 + 4xNow solve. Since it's second order, we'll probably get two answers.

x

^{2}-4x + 3 = 0(x - 3)(x - 1) = 0

x = 3, x = 1

Now check the answers

x

^{2}= -3 + 4x(3)

^{2}= -3 + 4(3)9 = -3 + 12

so that one checks

(1)

^{2}= -3 + 4(1)1 = -3 + 4

and that checks too.

So the answers are 3 and 1.